Introduction to molecular exercise physiology - Wackerhage, H. (Genetics and molecular biology of muscle adaptation, 2006)
CHAPTER CONTENTS Learning Objectives 121 Introduction 122 DNA 123 Transcription, RNA Capping and Splicing 124 Translation 127 Adaptation and Signal Transduction 128 Muscle Adaptation to Exercise 129 Regulation of Cellular Adaptation 130 Translational Regulation 138 Regulation of Gene Expression by siRNA and miRNA 138 Experimental Models 138 Muscle Cell Culture 138 Primary Cell Cultures 139 Secondary Cell Cultures 139 Satellite Cell Culture 140 Isolated Skeletal Muscle Studies 141 In Vivo Animal Experiments 141 Voluntary Running in a Running Wheel 142 Forced Treadmill Running 142 Electrical Low-frequency Stimulation 142 Models Inducing Muscle Hypertrophy 142 Transgenic Animals 143 Human Exercise Studies 144 Human Muscle Biopsy 144 Analytical Methods 145 DNA Methods 145 RNA Methods 152 DNA Microarrays 153 Protein Methods 155 Bioinformatics 158 Genome Browsing 159 Key Points 160 References 160